Treatment of hereditary angioedema—single or multiple pathways to the rescue - Valerieva, Anna; Longhurst, Hilary J. (Frontiers in Allergy, 2022)
Hereditary angioedema (HAE) is a rare disease caused by mutations in the SERPING1 gene. This results in deficient or dysfunctional C1 esterase inhibitor (C1-INH) and affects multiple proteases involved in the complement, contact-system, coagulation, and fibrinolytic pathways. Current options for the treatment and prevention of HAE attacks include treating all affected pathways via direct C1-INH replacement therapy; or specifically targeting components of the contact activation system, in particular by blocking the bradykinin B2 receptor (B2R) or inhibiting plasma kallikrein, to prevent bradykinin generation. Intravenously administered plasma-derived C1-INH (pdC1-INH) and recombinant human C1-INH have demonstrated efficacy and safety for treatment of HAE attacks, although time to onset of symptom relief varied among trials, specific agents, and dosing regimens. Data from retrospective and observational analyses support that short-term prophylaxis with intravenous C1-INH products can help prevent HAE attacks in patients undergoing medical or dental procedures. Long-term prophylaxis with intravenous or subcutaneous pdC1-INH significantly decreased the HAE attack rate vs. placebo, although breakthrough attacks were observed. Pathway-specific therapies for the management of HAE include the B2R antagonist icatibant and plasma kallikrein inhibitors ecallantide, lanadelumab, and berotralstat. Icatibant, administered for treatment of angioedema attacks, reduced B2R-mediated vascular permeability and, compared with placebo, reduced the time to initial symptom improvement. Plasma kallikrein inhibitors, such as ecallantide, block the binding site of kallikrein to prevent cleavage of high molecular weight kininogen and subsequent bradykinin generation. Ecallantide was shown to be efficacious for HAE attacks and is licensed for this indication in the United States, but the labeling recommends that only health care providers administer treatment because of the risk of anaphylaxis. In addition to C1-INH replacement therapy, the plasma kallikrein inhibitors lanadelumab and berotralstat are recommended as first-line options for long-term prophylaxis and have demonstrated marked reductions in HAE attack rates. Investigational therapies, including the activated factor XII inhibitor garadacimab and an antisense oligonucleotide targeting plasma prekallikrein messenger RNA (donidalorsen), have shown promise as long-term prophylaxis. Given the requirement of lifelong management for HAE, further research is needed to determine how best to individualize optimal treatments for each patient.